2020
DOI: 10.3390/medicina56100551
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Positive End-Expiratory Pressures Using Supreme™ Airway Laryngeal Mask during Minor Surgical Procedures in Children

Abstract: Background and objectives: The laryngeal mask is the method of choice for airway management in children during minor surgical procedures. There is a paucity of data regarding optimal management of mechanical ventilation in these patients. The SupremeTM airway laryngeal mask offers the option to insert a gastric tube to empty the stomach contents of air and/or gastric juice. The aim of this investigation was to evaluate the impact of positive end-expiratory positive pressure (PEEP) levels on ventilation paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Bonhomme et al, have evaluated the Surgical Pleth Index (SPI, GE Healthcare, Helsinki, Finland) trend and have made correlations with variability in mean arterial pressure and heart rate. Following this study they have shown that there is a strong correlation between all these variables and therefore SPI values depend on the doses of opioid medication administered during the anesthesia [58]. Bergmann et al, have carried out a randomized study that included 170 patients receiving general anesthesia with propofol and remifentanil.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Bonhomme et al, have evaluated the Surgical Pleth Index (SPI, GE Healthcare, Helsinki, Finland) trend and have made correlations with variability in mean arterial pressure and heart rate. Following this study they have shown that there is a strong correlation between all these variables and therefore SPI values depend on the doses of opioid medication administered during the anesthesia [58]. Bergmann et al, have carried out a randomized study that included 170 patients receiving general anesthesia with propofol and remifentanil.…”
Section: Figurementioning
confidence: 99%
“…The aim of these parameters is to come as an aid to the clinician in deciding the adequate analgesia dosage for each patient. While monitoring the degree of hypnosis is achieved through the direct evaluation of the EEG signals, the nociceptionantinociception balance can be monitored indirectly [9,12], by evaluating certain variables such as the vasomotor reflex, pupillary size, the H reflex, and the hemodynamic response [57][58] (Figure 1).…”
Section: Monitoring Techniques For the Nociception-antinociception Balancementioning
confidence: 99%
“…The aim of these parameters is to aid the clinician in deciding the adequate analgesia dosage for each patient. Whereas monitoring the degree of hypnosis is achieved through the direct evaluation of the EEG signals, the nociception-antinociception balance can be monitored indirectly [ 9 , 12 ] by evaluating certain variables such as the vasomotor reflex, pupillary size, the H reflex, and the hemodynamic response [ 57 , 58 ] ( Figure 1 ).…”
Section: Monitoring Techniques For the Nociception-antinociceptionmentioning
confidence: 99%
“…Following this study, they showed that there is a strong correlation between all these variables. Therefore SPI values depend on the doses of opioid medication administered during the anesthesia [ 58 ]. Bergmann et al carried out a randomized study that included 170 patients receiving general anesthesia with propofol and remifentanil.…”
Section: Monitoring Techniques For the Nociception-antinociceptionmentioning
confidence: 99%
“…The aim of these parameters is to come as an aid to the clinician in deciding the adequate analgesia dosage for each patient. While monitoring the degree of hypnosis is achieved through the direct evaluation of the EEG signals, the nociception-antinociception balance can be monitored indirectly [9,12,57], by evaluating certain variables such as the vasomotor reflex, pupillary size, the H reflex, and the hemodynamic response [58] (Figure 1). Figure 1.…”
Section: Monitoring Techniques For the Nociception-antinociception Bamentioning
confidence: 99%